Ultrasonic visualization technique for anatomical and functional analyses of the sciatic nerve in rats - Xu, Xiao-Dong; Lin, Lei; Qiu, Yu-Bei; Zeng, Bang-Wei; Chen, Ye; Liu, Jun-Le; Ye, Cai-Hong; Wang, Jia-Li; Liu, Pei-Chang; Zhang, Liang-Cheng (Frontiers in Neuroscience, 2023)
Background and objective Ultrasound has been widely used in the diagnosis and minimally invasive treatment of peripheral nerve diseases in the clinic, but there is still a lack of feasibility analysis in rodent models of neurological disease. The purpose of this study was to investigate the changes in the cross-sectional area of the sciatic nerve of different genders and body weights and to explore the effectiveness and reliability of an ultrasound-guided block around the sciatic nerve in living rats. Methods Using ultrasound imaging anatomy of the sciatic nerve of rats, the cross-sectional area of the sciatic nerve in rats of different genders from 6 to 10 weeks old was calculated, and then analyzed its correlation with body weight. Further analyses were conducted through behavioral and cadaveric studies to evaluate the feasibility of ultrasound-guided perineural injection of the sciatic nerve in rats. Results We first reported that the sciatic nerve cross-sectional area of rats was increased with age (F = 89.169, P < 0.001), males had a higher sciatic nerve cross-sectional area than females (F = 60.770, P < 0.001), and there was a positive correlation with body weight (rMale = 0.8976, P < 0.001; rFemale = 0.7733, P < 0.001). Behavioral observation of rats showed that the lower extremity complete block rate was 80% following the administration of drugs around the sciatic nerve under ultrasound guidance and staining with methylene blue occurred in all sciatic nerves and surrounding muscles and fascia using 20 ultrasound-guided injections. Conclusions Ultrasound visualization technology can be used as a new auxiliary evaluation and intervention therapy for animal models of peripheral nerve injury, and will provide overwhelming new references for the basic research of neurological diseases.